A survey of hypercalciuria during chemotherapy in acute lymphoblastic leukemia. Issue 8 (23rd June 2021) - Hori, Daiki; Kobayashi, Ryoji; Suzuki, Daisuke; Kodama, Koya; Yanagi, Masato; Matsushima, Satoru; Kobayashi, Kunihiko
Abstract: Background: Urolithiasis is an extremely rare complication in childhood acute lymphoblastic leukemia (ALL), and some reports have implicated corticosteroids during chemotherapy as a risk factor for it. However, only a few reports have analyzed urinary electrolytes in this context. Methods: We retrospectively analyzed 55 patients with ALL who underwent chemotherapy between October 2007 and January 2019. Their median age was 9.3 years (range, 0.3–24.0 years) with 30 males and 25 females. Lineages were B‐cell precursor ALL (BCP‐ALL) in 42 patients, T‐cell in nine and others in four patients. All patients received chemotherapy based on the Berlin‐Frankfurt‐Münster regimen. Results: Forty‐nine out of the 55 ALL patients exhibited hypercalciuria at least once during chemotherapy. Moreover, 36 patients with BCP‐ALL, who were receiving identical Berlin‐Frankfurt‐Münster‐based regimens, exhibited significantly high urinary calcium excretion immediately following high‐dose glucocorticoid administration. Among the 55 ALL patients, urolithiasis was observed in one patient, a 6‐year‐old boy with BCP‐ALL who developed urolithiasis at reinduction chemotherapy just after cessation of high‐dose dexamethasone administration. Conclusions: Nearly 90% of the ALL patients studied developed hypercalciuria during chemotherapy in strong association with corticosteroid administration.